2020
DOI: 10.1080/09553002.2021.1844335
|View full text |Cite
|
Sign up to set email alerts
|

Total body irradiation models in NHPs – consideration of animal sex and provision of supportive care to advance model development

Abstract: Purpose: Harmonized animal models are an indispensable tool for the development of safe and effective medical countermeasures (MCMs) against radiation injury, and rhesus macaques (referred herein as NHPs) play a critical role in FDA approval of radiation medical countermeasures for acute and delayed radiation syndromes. Reliance on such models requires that they be well characterized, which consists, in part, of a reproducible dose to mortality response relationship (DRR). However, data describing the DRR for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 10 publications
1
8
0
Order By: Relevance
“…Additionally, a recent analysis of research site-specific datasets noted as "historical" and "range-finding" provided DRRs using 60 Co gamma radiation plus medical management. The datasets showed that adult, male rhesus macaque, (a) were more sensitive to the lethal H-ARS than the datasets published above and that, (b) female rhesus macaques were markedly more sensitive than the male counterparts (Beach et al, 2020). Four of the studies noted previously, posted equivalent DRRs and slopes that estimated LD50/60 values that ranged from 7.43 to 7.54 Gy for male rhesus administered full supportive care (Farese et al, 2012;Thrall et al, 2015;Yu et al, 2015;Thrall et al, 2020) .…”
Section: High Dose Potentially Lethal Bilateral Uniform Tbi Exposure ...mentioning
confidence: 78%
See 3 more Smart Citations
“…Additionally, a recent analysis of research site-specific datasets noted as "historical" and "range-finding" provided DRRs using 60 Co gamma radiation plus medical management. The datasets showed that adult, male rhesus macaque, (a) were more sensitive to the lethal H-ARS than the datasets published above and that, (b) female rhesus macaques were markedly more sensitive than the male counterparts (Beach et al, 2020). Four of the studies noted previously, posted equivalent DRRs and slopes that estimated LD50/60 values that ranged from 7.43 to 7.54 Gy for male rhesus administered full supportive care (Farese et al, 2012;Thrall et al, 2015;Yu et al, 2015;Thrall et al, 2020) .…”
Section: High Dose Potentially Lethal Bilateral Uniform Tbi Exposure ...mentioning
confidence: 78%
“…The respective datasets are described below. A cumulative comparison will be made relative to respective published studies, DRRs and cellular kinetics that characterized the H-ARS for rhesus macaques exposed to bilateral or rotational TBI with 2 Mev x radiation, 60 Co gamma radiation and LINAC-derived photons or x rays (Dalrymple et al, 1965;Farese et al, 2012;MacVittie et al, 2015b;Thrall et al, 2015;Yu et al, 2015;Beach et al, 2020;Thrall et al, 2020) Drouet M and Herodin F (data herein); cynomolgus and rhesus macaques, 8.0 Gy, 7 Gy, 6.5 Gy, unilateral, AP, TBI 60 Co gamma radiation, plus medical management.…”
Section: Chen Et Al (2010)mentioning
confidence: 99%
See 2 more Smart Citations
“…Four sex matched NHPs ( Macaca mulatta ; Chinese sub-strain) weighing 4.0–8.3 kg and approximately 2–5 years old were used in this PK study. Young adult animals were used for this PK and metabolomics study because they are used in efficacy studies of H-ARS in NHPs exposed to TBI 44 46 . The animal study was conducted at Citoxlab, A Charles River Company (Laval, QC, Canada).…”
Section: Methodsmentioning
confidence: 99%